Publication Bias in Kienbock's Disease: A Systematic Review - Squitieri, Lee (J Hand Surg Am, 2010)
PURPOSE: Kienbock's disease is considered a “rare disease” and currently affects less than 200,000 people in the U.S. Given the inherent challenges associated with researching rare diseases, the intense effort in hand surgery to treat this uncommon disorder may be susceptible to publication bias in which positive outcomes are preferentially published. The specific aim of this project is to conduct a systematic review of the literature with the hypothesis that publication bias is present for the treatment of Kienbock's disease. METHODS: We conducted a systematic review of all available abstracts associated with published manuscripts (English and non-English) and abstracts accepted to the 1992-2004 American Society for Surgery of the Hand (ASSH) annual meetings. Data collection included various study characteristics, direction of outcome (positive, neutral/negative), complication rates, mean follow-up time, time to publication, and length of patient enrollment. RESULTS: Our study included 175 (124 English, 51 non-English) published Kienbock's manuscripts and 14 Kienbock's abstracts from the 1992-2004 annual ASSH meetings. Abstracts from published manuscripts were associated with a 53% positive outcome rate, which is lower than the 74% positive outcome rate found among other surgical disorders. Over the past 40 years, studies have become more positive (36% to 68%, p = 0.007) and are more likely to incorporate statistical analysis testing (0% to 55%, p <0.001). Of the 14 abstracts accepted to ASSH, 11 (79%) were published in peer-reviewed journals. Ten of the 14 accepted abstracts (71%) were considered positive, and there was no significant difference in publication rate between studies with positive (n = 10) and non-positive (n = 4) outcomes (p = 1.000). CONCLUSIONS: The acceptance rate for negative outcomes studies regarding Kienbock's disease is higher than for other surgical disorders. This may indicate a relative decrease in positive outcome bias among published Kienbock's studies compared to other surgical disorders. However, the increasing positive outcome rate for published Kienbock's studies over time may suggest a trend of increasing publication bias among journals toward Kienbock's studies.